Oxidative, Inflammatory, and Constipation Stress Modulation by a Heteropolysaccharide from Lacticaseibacillus rhamnosus CRL75 - René Emanuel Lobo; Ana Magdalena Ávila; Jonathan Laiño; Verónica Molina; Diego Navarro; María Inés Gómez; María Inés Torino; María Pía Taranto (Fermentation)
Lacticaseibacillus (L.) rhamnosus CRL75 is a lactic acid bacterium (LAB) isolated from local dairy products, demonstrating significant adaptation in skimmed milk (FM75). In this context, CRL75 exhibited high microbial growth (3.63 ± 0.18 log CFU·mL−1), strong acidification (9.20 ± 0.10 g·L−1 lactic acid, and 2.40 ± 0.10 pH units), and increased viscosity in FM75 after 16 h of fermentation. Additionally, this LAB strain produces both capsular polysaccharides (CPS+) and extracellular polysaccharides (EPS75), contributing to a ropy phenotype (>10 cm). The purified EPS75 (70.70 ± 3.25 mg·L−1) displayed low molecular weight (12.7 kDa), with galactose and glucose as its primary monomers in a 4:1 ratio. In aqueous environments, EPS75 exhibited an extended size (147 nm), a random coil structure, and macromolecular aggregation. Furthermore, vibrational spectroscopy confirmed the presence of a neutral EPS with high thermal stability. Additionally, EPS75 exhibited dose-dependent antioxidant activity, effectively reducing metal ions (Fe3+, Mo6+, and Mn7+) and stabilizing radicals (ABTS•+, HO•, O2•−, and HOO•). The biopolymer also demonstrated immunostimulatory and anti-inflammatory effects in RAW 264.7 cells. In vivo assays using Balb/c mice indicated that both EPS75 and FM75 prevented constipation, suggesting their potential as natural and safe agents for constipation-related disorders. Due to its viscosifying and health-promoting attributes, CRL75 offers promising applications for functional dairy products.